The Study of health literacy in pregnant women with nausea and vomiting - Zahra Kamali; Zahra Abedian; Ala sabermohamad (Mashhad University of Medical Sciences, 2017)
Background and objective: The health literacy includes person's capacity to learn and interpret information. Nausea and vomiting in pregnancy is the most common medical condition in pregnancy first three months that can be stressful for pregnant women and the family. The important role of health literacy in understands the risks before birth by mothers. The objective of this study was determining the health literacy of women with nausea and vomiting in pregnancy. Methods:In a cross-sectional study, 100pregnant women who referred to treatment centers in Neishabur County in year 2015 were investigated using the short test of functional health literacy and modified-PUQE. After confirming the validity and reliability were used. Data were analyzed using SPSS software. Results: According to the findings, the age average of participants was25.80%, 81.7%of samples were housewife,21.7%below high school diploma,and47%had average income.45.8 %of subjects had inadequate literacy level,35.6%border health literacy and18.6%had enough health literacy. Health literacy had significant association with Chi-Square Tests with, mother's education level and age (p